The effectiveness of high-intensity interval training on cardiometabolic outcomes in middle-aged and elderly populations with chronic diseases: a systematic review and meta-analysis - Li, Qiang; Xu, Gang; Liu, Chunai; Gao, Lina; Yu, Hongli (Frontiers in Physiology, 2025)
ObjectiveTo assess the effectiveness of High-Intensity Interval Training (HIIT) on cardiometabolic outcomes in Middle-Aged and Elderly Populations (MAEP) with chronic diseases.MethodsFour databases (PubMed, Cochrane Library, Embase, and Web of Science) were searched from inception to May 50, 2025. Software package RevMan version 5.4 and Stata 18 were conducted to determine publication bias and randomized controlled trials (RCTs) exploring the impacts of HIIT to components of high-density lipoprotein cholesterol (HDL-C), systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood glucose (BG), and triglyceride (TG) on MAEP with chronic diseases. Subgroup moderator analyses were conducted based on the intervention duration and geographic region.ResultsOut of 6,106 studies, 21 RCTs involving 1,066 participants were included. HIIT significantly benefits for DBP (SMD = −0.23, 95% CI: −0.39 to −0.08, p < 0.01), HDL-C (SMD = 0.41, 95% CI: 0.11 to 0.71, p < 0.01), TG (SMD = −0.68, 95% CI: −1.20 to −0.16; p < 0.05) and BG (SMD = −0.37, 95% CI: −0.69 to −0.06; p < 0.05), However, HIIT did not significantly reduce SBP (SMD = −0.14, 95% CI: -0.38 to 0.11, p > 0.05) among MAEP with chronic diseases. Subgroup analyses suggested that HIIT protocols with intervention duration and geographic region significantly reduced heterogeneity for outcomes such as SBP and HDL-C.ConclusionWhile HIIT did not significantly reduce SBP, it yielded meaningful benefits for DBP, HDL-C, TG, and BG in MAEP with chronic diseases. The findings suggest that the effectiveness of HIIT may vary by region and intervention duration, highlighting the importance of tailoring HIIT protocols to specific populations and contexts.Systematic Review Registrationidentifier CRD420251063576.